Erythrocytosis due to PHD2 Mutations: A Review of Clinical Presentation, Diagnosis, and Genetics - Rachel Wilson; Nausheen Syed; Prabodh Shah (Case Reports in Hematology)
The association of mutations in the PHD2 protein of the hypoxia-sensing pathway and erythrocytosis has only been established in the last decade. Here we report the case of a novel PHD2 gene mutation in a patient with erythrocytosis and summarize all reported cases to date. Case Report. A 55-year-old man presented with dyspnea and a previous diagnosis of idiopathic erythrocytosis. PHD gene sequencing revealed a mutation on exon 2. The mutation was recognized as p.(Trp334⁎) (c. 1001G>A) resulting in a truncation of a highly conserved amino acid residue in catalytic domain. A diagnosis of erythrocytosis secondary to mutant PHD2 gene was made. Conclusions. Our findings indicate that with PHD2 mutations there is moderate erythrocytosis and erythropoietin (Epo) levels are generally low to normal. Two patients with PHD2 substitution mutations were found to have paraganglioma and one of these patients had a concurrent pheochromocytoma. In addition, one mutation was associated with sagittal sinus thrombosis. Given the severity of some of the clinical features of these mutations, we conclude that clinical guidelines should include the PHD2 mutation in the idiopathic erythrocytosis workup.